Antimicrobial and antioxidant properties of Boswellia sacra resin: extraction, evaluation, and formulation into a topical cream for dermatological applications - Al-Saban, Abdulhakim; Maad, Abdullah H.; Al-Sham, Ali Salman; Saad, Hammood Mohamed (Frontiers in Medicine, 2025)
BackgroundFrankincense (Boswellia sacra) Resin has been used in traditional medicine for millennia because of its anti-inflammatory, antibacterial, and wound-healing characteristics. Recent research has proved its medicinal promise, particularly against resistant bacterial strains and oxidative stress.ObjectiveThis study seeks to assess the antimicrobial and antioxidant properties of Boswellia sacra resin, extracted with ethanol, and to formulate a topical cream for dermatological use, specifically targeting skin infections and inflammatory conditions such as acne.MethodsTwo techniques were used to extract frankincense resin: maceration and Soxhlet. The well diffusion method was used to evaluate the antibacterial activity against Escherichia coli, Bacillus cereus, Pseudomonas aeruginosa, and Staphylococcus aureus. The DPPH radical scavenging test was used to determine antioxidant activity. We produced and assessed the physical characteristics of a cream formulation containing Boswellia sacra extract, such as texture, homogeneity, and spreadability.ResultsThe ethanol extract of Boswellia sacra demonstrated notable antibacterial efficacy, especially against Staphylococcus aureus, with an inhibition zone measuring 15 mm at a dosage of 100 mg/mL. The antioxidant activity exhibited a dose-dependent relationship, with Soxhlet extraction demonstrating superior radical scavenging activity (84.66%) relative to maceration. The developed cream exhibited superior organoleptic characteristics, such as homogeneity, smoothness, and spreadability, suggesting its suitability for topical use.ConclusionThe results validate the notable antibacterial and antioxidant characteristics of Boswellia sacra resin. The formulated cream is a viable option for addressing skin infections and inflammatory illnesses, integrating traditional applications with contemporary pharmacological compositions.